CEO Health and Corporate Governance - Matti Keloharju; Samuli Knüpfer; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2020)
Boards hire and fire CEOs based on imperfect information. Using comprehensive data on 28 cohorts in Sweden, we analyze the role of a potentially important attribute—CEO health—in corporate governance. Boards hire CEOs who are healthier than other high-skill professionals, in particular in mental health. After hiring, CEOs' health develops similarly to a control group of executives. Health predicts turnover, measured at appointment and during tenure. These results are consistent with boards appointing CEOs with health robust enough to withstand the pressures of the job, correcting mismatches occurring at the time of appointment, and responding expediently to health shocks.
Keywords: G34; I12; J24; J31; 330; CEOs; Corporate Governance; Executives; Mental Health; Physical Health